2016
DOI: 10.1186/s13287-016-0322-3
|View full text |Cite
|
Sign up to set email alerts
|

The trans-well coculture of human synovial mesenchymal stem cells with chondrocytes leads to self-organization, chondrogenic differentiation, and secretion of TGFβ

Abstract: BackgroundSynovial mesenchymal stem cells (SMSC) possess a high chondrogenic differentiation potential, which possibly supports natural and surgically induced healing of cartilage lesions. We hypothesized enhanced chondrogenesis of SMSC caused by the vicinity of chondrocytes (CHDR).MethodsHuman SMSC and CHDR interactions were investigated in an in-vitro trans-well monolayer coculture over a time period of up to 21 days. Protein expression was analyzed using histology, immunostaining, or enzyme-linked immunosor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 26 publications
0
36
0
Order By: Relevance
“…A possible strategy in the field of cartilage repair is to use cocultures of different cell types, usually with articular chondrocytes, instead of choosing only one [ 92 ]. In this regard, several promising attempts have been performed with bone-marrow [ 93 96 ], synovium [ 97 ], and adipose-derived [ 96 , 98 ] stem cells. IFP stem cells also present an enhanced chondrogenic potential when cocultured with articular chondrocytes [ 99 ] and most especially when cocultured in a structured manner (i.e., on top of the articular chondrocytes), instead of homogeneously mixing them, in an attempt to recapitulate the zonal characteristics of a progenitor population on top of the native articular cartilage [ 100 ].…”
Section: The Ifp Stem Cellsmentioning
confidence: 99%
“…A possible strategy in the field of cartilage repair is to use cocultures of different cell types, usually with articular chondrocytes, instead of choosing only one [ 92 ]. In this regard, several promising attempts have been performed with bone-marrow [ 93 96 ], synovium [ 97 ], and adipose-derived [ 96 , 98 ] stem cells. IFP stem cells also present an enhanced chondrogenic potential when cocultured with articular chondrocytes [ 99 ] and most especially when cocultured in a structured manner (i.e., on top of the articular chondrocytes), instead of homogeneously mixing them, in an attempt to recapitulate the zonal characteristics of a progenitor population on top of the native articular cartilage [ 100 ].…”
Section: The Ifp Stem Cellsmentioning
confidence: 99%
“…Activated synovial macrophages showed that enhanced in ammation mediated the chondrocyte microenvironment and promoted MMP accumulation, which resulted in degradation of extracellular matrix (ECM). [28][29][30] Consistently, ECM degradation acted as a DAMP, stimulating macrophage activation and increasing synovial in ammation, which resulted in positive feedback regulation of in ammation and cartilage degradation. Samavedi [31] et al demonstrated that chondrocytes co-cultured with macrophage activation expressed signi cantly enhanced in ammatory factors, resulting in ECM degradation.…”
Section: Discussionmentioning
confidence: 88%
“…Chondrocytes have been reported to secrete a range of soluble factors that promote chondrogenesis of MSCs during in vitro culture, regulating matrix remodeling, cell proliferation, and synthesis of extracellular matrix components by stem cells. For example, when combined in close proximity, mixed cell culture systems produced engineered cartilage with increased mechanical properties (Young's modulus and dynamic modulus), GAG levels, and collagen content . Interestingly, these chondrocytes were also able to decrease the deposition of collagen X , a marker of MSC hypertrophy, perhaps by secreting PTHrP .…”
Section: Chemical Stimulationmentioning
confidence: 99%
“…It is important to note that a more thorough characterization of the influence of these two cell systems on one another is necessary to fully realize the potential of coculture systems. While a number of studies have found positive effects from chondrocytes on MSC chondrogenic differentiation , other studies have found that the beneficial effects are due to the trophic role of MSCs in stimulating chondrocyte proliferation and matrix deposition . Notably, using a xenogenic system and species‐specific gene expression analysis to determine the contribution of various cell populations to cartilage formation, Wu et al showed that following coculture, micromass pellets contained predominantly DNA from the species of origin of the primary chondrocytes, indicating an overgrowth of chondrocytes or loss of MSCs during the culture period.…”
Section: Chemical Stimulationmentioning
confidence: 99%